SCIENTIFIC SUBSTANTIATION: FOR AND AGAINST 6-YEAR-OLD CHILDREN COMMENCING SCHOOL EDUCATION - Liduma, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The scientific article actualizes the pedagogical process at preschool. It actuates school year 2017/2018 pedagogical process for Latvia state’s needs and involves education (teaching and learning) and upbringing/self-upbringing (attitudes’ development to oneself, others, nature, work, culture, state and society). The assessment is provided for the open to debate Project No 8.3.1.1/16/I/002 “School 2030 Competence approach to education content” as the scientifically non-substantiated content, which makes provision only for education. The scientific substantiation of the article is based on the child development in early childhood (0-8 years) actual theories by A. Spona, A. Liduma, Latvian scientists, G. Craig & Baucum, the USA psychologists, and A. Rean, Russian psychologist. Analysis of the Content of Preschool education of the year 2012 by Latvian Ministry of Education and Science and the Cabinet of Ministers. The empirical research analyses different visions on the 6-year-olds’ maturity/readiness for school by the deputy head-masters in education at preschool education establishments of Latvia's regions. The opinions for and against the 6-year-olds’ education at school by children parents and the preschool pedagogy students have been analysed.